The percentage of male and female dream characters in a long dream series - Schredl, Michael (International journal of dream research, 2021)
Previous research based on many dream studies including children, adolescents, students, and adults in different cultures reported a “ubiquitous” sex difference in dreams: Whereas male dream characters are more prominent in men’s dreams compared to female dream characters, women tend to dream equally often about males and females. The present findings of 52% in a series of 3828 dreams recorded by a middle-aged male individual indicate that this gender difference might not be “ubiquitous” but depends on the pattern of waking-life social contacts. Studying the ratio of male and female dream characters might help to understand how social life is reflected in dreams.
Gesehen am 21.04.2021